The participating citizen : a biography of Alfred Schutz - Barber, Michael D., 1949- (Albany : State University of New York Press, 2004)
An in-depth biography of the philosopher who brought phenomenology to the social sciences.
Maturing in a troubled Vienna. -- Social science and philosophy (1919-38): Weber and Bergson. -- Philosophy and social science (1919-38): Husserl and Mises and Kelsen. -- Matters unpublished. -- Anschluss. -- Reestablishing. -- World War II years. -- Schutz, a Nihilist? -- Peace and productivity after the war (1945-51) -- The years 1952 to 1956: responsible life at its fullest. -- The years 1952 to 1956: philosophical midwifery: correspondence and research. -- The search for equality. -- Triumphs and decline, 1957-58. -- Death and new beginnings. -- Appendix: The courses Schutz taught.
Includes bibliographical references (pages 279-308) and index.
Print version record.
English.
JSTOR
Keywords: Schutz, Alfred, -- 1899-1959.; Schutz, Alfred, -- 1899-1959; Sociologists -- Austria -- Biography; Phenomenological sociology; Sociologues -- Autriche -- Biographies; Sociologie phénoménologique.; BIOGRAPHY & AUTOBIOGRAPHY -- Social Scientists & Psychologists; SOCIAL SCIENCE -- Regional Studies; SOCIAL SCIENCE -- Anthropology -- General; Phenomenological sociology; Sociologists; Austria; Biographies; Biographies; Biographies